On the Question of the Concept and Forms of Cyberbullying in Russia - POLISHCHUK, Nikolai Ivanovich; VOROBYOV, Sergei Mikhailovich; ORLOVA, Alexandra Andreevna; ABOVYAN, Edgar Parhamovich (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
Present article presents the analysis of such type of psychological violence as cyberbullying. The article explores negative phenomena that facilitate its distribution on the Internet and definitions of cyberbullying; it describes the danger of cyberbullying. The aim of the research is to develop the forms of cyberbullying as a type of psychological violence with regard to the level of its incidence and danger for the society and for a person in Russia. The work employed modern general-scientific and special methods of cognition: dialectic, systemic-structural, historical, formally-logical, formally-legal and statistical methods. The article presents the conclusion about the need in developing efficient measures of interference with this dangerous phenomenon by the state and civil society’s institutions.